By induction:
It's true for
, since
clearly contains a factor of 3.
Suppose it's true for
, that
is divisible by 3. Then
where
is an integer. This reduces to
and both terms are clearly multiples of 3. We know that
is an integer since we had set
previously, which implies
is a multiple of
. So the statement is true.
Answer:
6
Step-by-step explanation:
let the number be x
(x-2)3=x+6
3x-6 = x+ 6
2x= 12
x= 6
The answer to the question is a
Answer: x = -2, y = -10
Step-by-step explanation:
solve for x first in the equation -2x+3=7
-2x+3=7
-2x = 4
x = -2
now plug that x value into the other equation so we can find y
3x+1 = 5+y
3(-2)+1 = 5+y
-6+1 = 5+y
-5=5+y
-10 = y